2015
DOI: 10.1177/1708538115590727
|View full text |Cite
|
Sign up to set email alerts
|

One-year results of the ANCHOR trial of EndoAnchors for the prevention and treatment of aortic neck complications after endovascular aneurysm repair

Abstract: Despite a high frequency of hostile neck anatomy, proximal neck complications were relatively infrequent after EndoAnchor use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
2
26
2
2
Order By: Relevance
“…They found that freedom from type 1a endoleak was 95% in the primary arm and 77% in the revisions. Hostile necks were defined as those with a neck length of <10 mm, neck diameter >28 mm, or angulation >60°, or those with a conical configuration or significant mural thrombus or calcifications . Our experience extends the use of the EndoAnchors to shorter proximal aortic necks and further demonstrates the functionality of EndoAnchors in promoting proximal fixation.…”
Section: Discussionmentioning
confidence: 88%
“…They found that freedom from type 1a endoleak was 95% in the primary arm and 77% in the revisions. Hostile necks were defined as those with a neck length of <10 mm, neck diameter >28 mm, or angulation >60°, or those with a conical configuration or significant mural thrombus or calcifications . Our experience extends the use of the EndoAnchors to shorter proximal aortic necks and further demonstrates the functionality of EndoAnchors in promoting proximal fixation.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, EndoAnchor implants can increase aortic wall apposition and prevent migration during follow-up. 2,8,9 However, it is important to use the EndoAnchor implants in the same way as one would use a pledgeted suture (endovascular stitching). Thus, where sutures are used in case of a bleeding anastomosis, EndoAnchor implants can be used to resolve a type IA endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in patients unfit for open surgery and with short proximal neck (<15 mm in length) that is at least 7 mm long and up to 32 mm in diameter, our standard practice is to prefer the use of the Endurant stent-graft with the eventual adjunct of anchors, considering the relative simplicity of the procedure, the immediate availability of devices, and the satisfactory reported early- and mid-term results in terms of aneurysm exclusion and stability. 15,16,20,21 For those cases with a proximal neck shorter than 7 mm and/or wider than 32 mm that are not eligible for open surgery, there is the need to extend the proximal sealing zone above the renal arteries to prevent late complications in the follow-up, so we prefer to resort to other endoluminal techniques such as fenestrated stent-grafts, or chimney procedures when there is no possibility to wait for a custom-made device.…”
Section: Discussionmentioning
confidence: 99%